Efetividade das ações de educação ambiental para a segregação dos resíduos sólidos domiciliares em sistema de coleta por conteinerização no município de Antônio Prado-RS - Casagrande, Verônica (My University, 2017)
Integrated solid waste management has its effectiveness linked to planning, efficiency in the execution of public services and the commitment of the population to the participation of the waste management system. In municipalities where the containerization system is implemented, it is necessary to disseminate the information related to the concepts and importance of good practices of segregation in the generating source, in order to obtain effective results. The availability of information can occur through environmental education activities, which can be developed from the application of several methods and directed to different target audiences. This work aims to present the results of the evaluation of the effectiveness of environmental education actions implemented in the municipality of Antônio Prado, Rio Grande do Sul, Brazil, by means of the evaluation of the segregation of solid household waste from selective and regular collections, post implementation of containers. The applied method contemplated the physical characterization and gravimetric composition of solid wastes, as well as, documentary analysis and application of form to the resident population in a geographic sample unit. The results indicate that the alteration of the municipal waste collection system can lead to a reduction in the efficiency of waste segregation in the generating source. Regarding the effectiveness of environmental education actions, a significant improvement was identified in the segregation of waste after the implementation of educational actions in Antônio Prado. The results obtained in this work are relevant to the municipal unit, since they subsidize the planning and operationalization of public solid waste and environmental education services.
A gestão integrada de resíduos sólidos possui sua efetividade vinculada ao planejamento, à eficiência na execução dos serviços públicos e ao comprometimento da população na participação do sistema de gerenciamento de resíduos. Em municípios onde é implementado o sistema de conteinerização, é necessário disseminar as informações relacionadas aos conceitos e importância das boas práticas de segregação na fonte geradora, para que sejam obtidos resultados efetivos. A disponibilidade de informações pode ocorrer por meio de atividades de educação ambiental, que podem ser desenvolvidas a partir da aplicação de diversos métodos e direcionada para diferentes públicos-alvo. Este trabalho objetiva apresentar os resultados da avaliação da efetividade das ações de educação ambiental implementadas no Município de Antônio Prado, Rio Grande do Sul, Brasil, por meio da avaliação da segregação dos resíduos sólidos domiciliares provenientes das coletas seletiva e regular, em período pré e pós implementação de contêineres. O método aplicado contemplou a caracterização física e composição gravimétrica de resíduos sólidos, assim como, análises documentais e aplicação de formulário junto à população residente em uma unidade geográfica amostral. Os resultados indicam que a alteração do sistema municipal de coleta de resíduos pode propiciar a redução na eficiência da segregação de resíduos na fonte geradora. Quanto à efetividade das ações de educação ambiental, identificou-se relevante melhoria na segregação dos resíduos após a implementação de ações educativas em Antônio Prado. Os resultados obtidos neste trabalho são relevantes à unidade municipal, pois subsidiam o planejamento e a operacionalização dos serviços públicos de resíduos sólidos e educação ambiental.
Keywords: Resíduos sólidos - Antônio Prado (RS); Educação ambiental - Antônio Prado (RS); Gestão integrada de resíduos sólidos - Antônio Prado (RS); Solid wastes - Antônio Prado (Brazil); Environmental education - Antônio Prado (Brazil); Integrated solid waste mangement - Antônio Prado (Brazil)